Try it! : even more math problems for all - Kaplan, Jerry; Dercon, Ysemay (New York : Routledge, Taylor & Francis Group, 2024)
This is not your typical math book. Try It! Even More Math Problems for All is the third of three collections of offbeat, open-ended problems designed to make even the most math-averse student excited about working through these challenging yet accessible problems. The Hints and Solutions section guides you to probe, suggest, and encourage students to explore even their most unusual insights on the way to solving these 25 new, illustrated problems of varying difficulty. As a result, you will be able to motivate your students to think creatively on their own and to engage in teamwork. And when students solve a problem, you will see and hear their accomplishments. Perfect for any math classroom, club, after school activity, or coaching session, Try It! celebrates not only the destination, but the journey, giving students a chance to think differently, and, above all, have fun! Can't get enough? Volume 1 in the series, Try It! Math Problems for All, and Volume 2, Try It! More Math Problems for All, are also available at Routledge.com. Optional Student Workbook Packs In addition to this teachers' guide, companion student workbooks are available in packs of ten. The student workbooks feature ample room for student responses and notes, make reviewing and providing feedback on student work easy, provide students with a quick reference to use during discussions, and they save time - there is no need to reproduce student handouts.
Keywords: EDUCATION / Teaching Methods & Materials / Mathematics; JUVENILE NONFICTION / Activity Books; Mathematics -- Study and teaching (Elementary)